Learning from practice: The value of a personal learning coach for high-performance coaches - Rodrigue, F.; Trudel, P.; Boyd, J. (International Sport Coaching Journal, 2019)
Multiple actors and roles are now recognized and promoted to support the development of coaches. Personal coaching is an emerging industry in many professional fields yet remains insignificant in sport coaching. The purpose of this study was to document and assess the value of a 12-month collaborative action research in which a high-performance rugby coach, with the support of a personal learning coach, aimed to learn from her coaching practice. This research was operationalized using an appreciative inquiry framework. Personal coaching was conducted according to the principles of narrative-collaborative coaching. Data collection included interviews, video observation, audio recordings of coaching conversations, notes from phone calls, and email exchanges. Results showed that this partnership created a safe and challenging learning space where different coaching topics were addressed, such as reflective practice, leadership, and mental preparation. A deductive analysis of the debriefing interview was completed using the value creation framework developed by Wenger and colleagues. This analysis indicated that the high-performance coach`s relationship with the personal learning coach enabled the development of five types of value: immediate, potential, applied, realised, and transformative. Therefore, it is suggested that narrative-collaborative coaching can complement existing formal and non-formal learning activities.